Eksilsituation og profettradition - Otzen, Benedikt (Religionsvidenskabeligt Tidsskrift, 1988)
Opposition at Knud Jeppesen’s defence of his thesis “Græder ikke saa saare. Studier i Mikabogens sigte” (Aarhus Universitetsforlag 1987). Jeppesen advocates that the idea of the Book of Micah obtained its final shape through a redaction in Babylon during the exile. The criticism concentrates upon the question whether earlier redactions of the Micah traditions (between 8th and 6th centuries) had impact on later (exilic or post-exilic) redactions and thus would be of importance for the understanding of the final structure of the Book of Micah.